Synthesis and Characterisation of B-CDs/TiO2 Composite - Anthoni B. Aritonang; Ajuk Sapar; Uswatun Hasanah; Adhitiyawarman Adhitiyawarman; Puji Ardiningsih (Jurnal Akademika Kimia, 2022)
Synthesis of composite boron-doped carbon nanodots (B-CDs)/TiO2 using the sol-gel method performed with titanium tetraisopropoxide (TTIP) precursor and B-CDs prepared by the microwave method using citric acid monohydrate, urea, and boric acid as precursors. The optimum concentration of boron dopant (B) on B-CDs/TiO2 is 0.5% boron (w/w) which is then used as a composite on TiO2 resulting in a brown solid and has blue luminescent under UV light. The result with UV-Vis/DRS for variation in B-CDs concentration of 0.5%, 1.25%, and 2.5% showed Eg values of 2.34 eV, 2.00 eV, and 2.29 eV. B-CDs cause the maximum emission peak (λEm) to redshift and affect the intensity of photoluminescence TiO2. The characterization of FT-IR does not indicate a new peak, there is no bonding in the B-CDs/TiO2 composite. The TiO2 diffractogram was observed to shift towards a larger 2θ which caused the crystallinity of TiO2 to decrease. Based on the photocatalytic activity test on the degradation of methylene blue solution, it showed fairly good activity. It is expected that the B-CDs/TiO2 composite has the potential to be applied as a photocatalyst to degrade organic pollutants under visible light illumination.